Explosion risk-based water spray mitigation analysis of ultra-deep-water semi-submersible platforms. (1st November 2021) - Shi, Jihao; Li, Junjie; Khan, Faisal; Chang, Yuanjiang; Zhu, Yuan; Chen, Guoming
Abstract: Water spray is an economical and environment-friendly alternative to mitigate gas explosion. This study conducts explosion risk analysis (ERA)-based water spray mitigation analysis of ultra-deep-water semi-submersible platform. 5000 gas explosion simulations with and without water spray are conducted by using FLACS codes. The outcome demonstrates that water spray with droplet size 700 μm and water application rate ( WAR) 26 L/m 2 min is most effective to mitigate explosion scenarios. The droplet size is the significant factor to stimulate the mitigation effect of water spray under middle and small exceedance frequencies, e.g., 1E-05 and 1E-06. WAR becomes dominate to awaken the water spray's negative effect under large exceedance frequency, e.g., 1E-04. A precise and efficient approach of BRANN integrated with artificial bee colony optimization algorithm is used to determine the optimal water spray configuration given the desirable exceedance frequency and the expected design accidental load that the ultra-deep-water semi-submersible platform structures could resist. Highlights: Explosion risk mitigation analysis of water spray for ultra-deep-water semi-submersible platform is conducted. Large number of gas explosion simulations is carried out by using FLACS codes. Effect of water spray configuration on exceedance frequency is analyzed. Machine learning-based approach is proposed to determine the optimal water spray configuration.